Interpreting DTBZ binding data in rodent: Inherent variability and compensation. Issue 4 (27th January 2016) - Mejias, Miguel; Yu, Jing; Mackey, Scott; Dinelle, Katie; Sossi, Vesna; Doudet, Doris J.
ABSTRACT: [11C]‐dihydrotetrabenazine (DTBZ) Positron Emission Tomography was used to evaluate the vesicular monoamine transporter type 2 as an index of dopaminergic function in the striatum of adult Sprague‐Dawley rats obtained from two different animal sources (Charles River Laboratories [CR] or UBC's Animal Care Centre [ACC]) and later submitted to two different unilateral lesions of the nigro‐striatal pathway. The results showed a significant difference in the striatal binding potential (BPND ) at baseline (before lesioning) between the CR and ACC groups providing evidence that the origin of the animals, possibly due to differences in early environmental factors or breeding conditions associated with different animal vendors plays a role in the development of the adult dopaminergic system. Further, in both animal models, an increase in DTBZ BPND was observed, after unilateral intervention, in the striatum contralateral to the lesion, likely reflecting compensatory effects. Based on these findings, we conclude that in unilateral models, the unlesioned side/hemisphere may not be an appropriate control and that care should be taken to control for the origin of the animals in any given study, especially in longitudinal and replication studies. Synapse, 2016. © 2016 Wiley Periodicals, Inc. Synapse 70:147–152, 2016. © 2016 Wiley Periodicals, Inc. Abstract : The striatal binding of DTBZ at baseline between two groups of rats of same age, sex and strain but from different suppliers shows significant differences (**). Following unilateral lesion, the binding in the unlesioned striatum is significantly increased compared to baseline (*). Both observations affect accurate data interpretation.